COMPARISON OF STYLISTIC ELEMENTS ACROSS DIFFERENT WORKS OF BERNARD SHAW (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This study compares and contrasts Bernard Shaw's plays and prose in order to examine the stylistic features that set his writings apart. Shaw's work demonstrates his avant-garde approach to drama by fusing satire, wit, and comedy with insightful societal criticism. The recurrent themes of social reform, gender equality, and human advancement are highlighted as this research explores how Shaw's use of language, characterization, and dramatic structure changes over his various works. Shaw's creative variety and ideological consistency are highlighted by the research's identification of stylistic patterns and divergences through an analysis of famous texts such as Pygmalion, Major Barbara, and Man and Superman. By providing insights into how Shaw's writing adjusts to a variety of thematic themes while retaining its distinctive intellectual energy and rhetorical flare, the research seeks to advance our understanding of his distinctive literary style and its influence on contemporary theatre.